Electrocatalytic Deoxyfluorination of Benzyl Alcohols with SF6 as a Fluorinating Agent - Zhu, Shan; Zhao, Yue; Ma, Fengxiang; Song, Yumei; Liu, Wei; Cao, Jun; Abulikemu, Abudu Rexit; Wang, Xisheng (Synthesis, 2025)
Emerging as the basic structural units in a variety of bioactive molecules, developing straightforward and efficient methods for synthesizing benzylic fluorinated compounds is of considerable significance. Herein, an electrocatalytic strategy utilizing sulfur hexafluoride (SF6) as a fluorinating reagent to transform benzylic alcohols into benzyl fluorides has been developed under mild conditions. This reaction is compatible with several substrate backbones and avoids the excessive usage of chemical reductants, which provides new routes for the efficient utilization and degradation of SF6, the potent greenhouse gas.
Keywords: Electrocatalysis; Deoxyfluorination; Sulfur hexafluoride; Benzyl alcohol; C–F bond